Radiosensitizing effects of pyrogallol-loaded mesoporous or-ganosilica nanoparticles on gastric cancer by amplified ferroptosis - Wang, Hongwei; Niu, Hongyan; Luo, Xi; Zhu, Nan; Xiang, Jingfeng; He, Yan; Chen, Zhian; Li, Guoxin; Hu, Yanfeng (Frontiers in Bioengineering and Biotechnology, 2023)
Radiotherapy (RT) incorporated multidisciplinary treatment is producing excellent clinical results, but its efficacy in treating late-stage gastric cancer is constrained by radioresistance and RT-related toxicity. Especially, since reactive oxygen species are the pivotal effectual molecules of ionizing radiation, improving ROS production by nanoparticles and other pharmacological modulation to amplify oxidation of polyunsaturated fatty acids and subsequent ferroptotic cell death is shown to enhance cancer cell radioresponse. Herein, we constructed a nanosystem by loading Pyrogallol (PG), a polyphenol compound and ROS generator, into mesoporous organosilica nanoparticles named as MON@PG. The nanoparticles exhibit proper size distribution with amplified ROS production and substantial glutathione depletion under X-ray radiation in gastric cancer cell line. Meanwhile, MON@PG enhanced radiosensitivity of gastric cancer in xenograft tumor model by ROS-mediated accumulation of DNA damage and apoptosis. Furthermore, this augmented oxidative process induced mitochondrial dysfunction and ferroptosis. In summary, MON@PG nanoparticles show the capacity to improve RT potency in gastric cancer by disrupting redox balance and augmenting ferroptosis.